Asisten Navigasi untuk Orang dengan Gangguan Penglihatan Menggunakan Ultra Sonic (Sonar Vision) Untuk Yayasan Mitra Netra - Rudi Susanto (Bina Nusantara University, 2020)
Generally, people with visual impairments in the low vision category use sticks to find ways to deal with obstacles in front of them. However, this detection can only be felt as long as the stick is used. The purpose of this community service activity is to made a sonar vision set using a sonar sensor that can be attached to the wrist and belt. This device is designed to detect obstacles up to a distance of 3 meters. This activity was carried out at the Mitra Netra Foundation. The approach used is the creation, provision and education of the use of the Sonar Vision module for people with visual impairments. The results of this activity show that 100 low vision sufferers have benefited from this system, where 84% of them feel that sonar vision helps them in navigation.